Podospora anserina bibliography n° 10 - Additions - Robert Debuchy (Fungal Genetics Reports, 2003)
Podospora anserina is a coprophilous fungus growing on herbivore dung. It is a pseudohomothallic species in which ascus development results, as in Neurospora tetrasperma but through a different process, in the formation of four large ascospores containing nuclei of both mating types.